Unhealthy traits and risk of Parkinson's disease: a mendelian randomisation study. Issue 6 (27th May 2022) - Jensen, Melanie; Heilbron, Karl; Bandres-Ciga, Sara; Fontanillas, Pierre; Blauwendraat, Cornelis; Nalls, Mike; Singleton, Andrew; Smith, George Davey; Cannon, Paul; Noyce, Alastair
Abstract : Introduction: Observational studies have flagged smoking, alcohol and high body mass index (BMI) as potential protective factors against Parkinson's disease (PD), however it is unclear whether such asso- ciations are causal. Mendelian randomisation (MR) uses gene variants to explore causal trait-outcome effects, minimising bias from observational studies. Using MR, we sought to determine the causal relation- ship between unhealthy traits (tobacco smoking, alcohol intake, and high BMI) and PD risk. Methods: We used genome-wide association studies to find single nucleotide polymorphisms associated with each trait. Using split-sample MR, we used inverse weighted (IVW) methods to determine the effect of traits on PD. We used MR-Egger and weighted mean methods to check for bias in IVW analyses. Results: Ever-smoking and high BMI causally reduced PD risk (OR 0.96 95%CI 0.92–0.99 p=0.01; OR 0.99 95%CI 0.98–1.00 per 1 kg/m2 p=0.01, respectively). Alcohol causally increased PD risk (OR 1.13 95%CI 1.03–1.24 p=0.01). Sensitivity analyses did not reveal bias from pleiotropy or invalid instruments. Conclusions: MR analysis in over 2.4 million participants showed a protective effect of smoking on PD; war- ranting prioritisation of related therapeutic targets in clinical trials. Conversely, alcohol causally increased PD risk. Higher BMI protected against PD, but the effect was marginal. m.jensen@cantab.net